Pedagogical attitudes/perceptions of college writing center peer tutors towards the process of tutoring - Ackerman, Patricia E. (Kansas State University, 2007)
This study poses questions about the nature of tutoring processes in college level writing centers. As tutors engage student writers, they are presented with complex rhetorical and interpersonal decisions. This researcher seeks to understand deliberate strategies and thought processes applied by tutors to encourage critical thinking abilities in students. How do writing center tutors decide which strategies are needed for different tutoring situations? How do they perceive the reasons why they themselves apply particular strategies? In order to explore these and other questions, the researcher observes tutorial sessions conducted by ten college-level writing center tutors. Triangulated research methodologies are applied, including observation/video-taping, audio-taped think-aloud protocols, transcribed text analysis, a group exit interview, and external collaborator analysis. Immediately following each video-taped tutorial session, the researcher views the video-tape with each respective tutor. Following instruction in think-aloud protocol process, tutors are asked to reflect orally on the process and decision-making strategies applied throughout the tutorial session. Each of these think-aloud sessions is audio-taped. All ten of the video-taped and audio-taped tutorial sessions are then transcribed and coded for thematic patterns. Two credible outside co-raters are asked to analyze the texts, as well, providing interater reliability. Conclusions and implications about how writing center peer tutor perceive individual strategies applied in tutorial sessions are considered. How do tutors decide what types of questions and comments to ask? How do they facilitate the process of fostering student learning and critical thinking? What are the perceived barriers to success in each session?
Keywords: Writing centers; Peer tutors; Thinkaloud protocols; Rhetoric and composition; Tutorial Discourse; Retrospective thinkaloud protocols; Education, Curriculum and Instruction (0727); Education, Language and Literature (0279); Language, Rhetoric and Composition (0681)